Social work supervision in six regional offices of the Department of Health Services and Welfare (Administration : House of Assembly) - Weekes, Michael Seymour; South Africa.Administration: House of Assembly.Dept. of Health Services and Welfare (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1987.